Variabilitas dan Heritabilitas Karakter Penting beberapa Genotip Padi Sawahpada Cekaman Salinitas Tinggi - Roni Assafaat Hadi; Raden Budiasih (Paspalum: Jurnal Ilmiah Pertanian, 2015)
The objective of the research was to know the variability and heritability some field rice genotype important characters on high salinity pressure. The research was carried on Laboratory and Screen House of Balai Pengawasan dan Sertifikasi Benih Tanaman Pangan dan Hortikultura, Bandung with the altitude is 600 m above sea level. The time of the research was started on October 2011 until February  2012. The research used experimental methods and Randomized Block Design with 16 field rice genotype and replicated 2 times. The main observation variables are plant height, weight of dry shoot, weight of dry root, relativity of shoot and root, age of flowering, age of harvest, number of tassel per plant, number of rice per plant, percentage of empty rice per plant, weight of 1000 grain seeds per plant and result of unhulled rice per plant. The research and also showing different expected value heritability for important characters of field rice on high salinity pressure. High heritability value held by age of harvest 0,52; number of tassel per plant 0,95; number of rice per plant 0,978; percentage of empty rice 0,96 and weight of 1000 grain seeds 0,81 characters. For plant height 0,31 and age of flowering 0,42 characters including to middle heritability. While for low heritability value there are weight of dry shoot -0,028;weight of dry root -0,082; relativity of shoot and root -0,25 and result of unhulled rice per plant 0,11 characters.